PENDAMPINGAN DAN INOVASI PRODUKSI MINUMAN HERBAL PENJAGA IMUNITAS KHAS NGAWI JAWA TIMUR - Novia Enka Purnamasari; Yudha Nurdian (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
The spread of Covid-19 has widened to have an impact in rural areas, one of which is Geneng village, Geneng District, Ngawi Regency. Many of the people of Geneng village are affected in various areas of their livelihood, including as employees of a textile factory, bridal makeup, school canteen keepers, building contractors (migrants) so that the village community becomes unemployed. The condition of the spread of the Covid-19 pandemic is also very worrying in the health sector, the need for all elements to maintain body immunity. The Back To Villange Real Work Lecture Program at the University of Jember provides concrete evidence of providing entrepreneurial empowerment for people affected by Covid-19 with the herbal beverage entrepreneurial innovation work program "JABAL". The method is carried out with several work programs including the introduction of target communities, manufacturing products, marketing products, and making kkn classes. Introduction of target communities by providing socialization of work programs, K3 training with target communities. Products produced that have collaborated with the target community consist of 5 variants, namely ginger, kencur, turmeric, ginger and wedang uwuh. The manufacture is in collaboration with five target village communities and the recipe for the product is obtained from recipes derived from their ancestors. Product packaging also needs to be paid attention to where the product packaging includes three things, namely brand, packaging and label. Product marketing is carried out online and offline. The program was carried out with the aim of helping people whose work was affected by Covid-19 and developing the potential of Geneng Village, Geneng District, Kab. Ngawi.